Initiating Practice Guidelines for Postpartum Depression Screening at Well-Child Visits - Sessoms, Andrea D. (My University, 2014)
Purpose: This project examined the process of initiating postpartum depression (PPD) screening via a PPD protocol at 2 month well-child visit in four pediatric/family practice offices in a rural North Carolina county. The goal is to foster organization improvements to integrate maternal PPD screening into routine pediatric practice. Study Design and Methods: The design is a prospective analysis of the process of initiating a PPD protocol into clinical practice. This protocol was developed based on information and recommendations gathered from the literature review. Mothers were administered the Edinburgh Postnatal Depression Scale (EPDS) at the two month well-child visit. Women who scored 10 or greater would be identified as at risk for PPD and would be counseled by the pediatric provider about PPD, provided two educational handouts and given a referral appointment with their delivery obstetrician. Results: Fourteen PPD screens were performed identifying one mother as at risk and referred. Overall, initiating PPD screens in these pediatric offices was easy, cost effective and did not cause an increase in workload of the providers or nurses. Clinical Implications: In an effort to increase the screening, identification and referrals for mothers with PPD, one has to examine other health care settings, such as well-child visits, where this screening can take place. Initiating the screening at the pediatric well-child visits provides an additional opportunity to screen mothers. Increasing the detection rates for postpartum depression is imperative to improve the health of not only the mother, but also of the infant and family (AAP, 2010).
Keywords: Well-child visits; Edinburgh Postnatal Depression Scale; Postpartum depression screening